Natalizumab discontinuation and disease restart in pregnancy: a case series. (18th January 2015) - De Giglio, L.; Gasperini, C.; Tortorella, C.; Trojano, M.; Pozzilli, C.
<x xml:space="preserve">Abstract</x> Background The humanized monoclonal alpha4‐integrin antibody Natalizumab (NTZ) (Tysabri©, Biogen Idec, Cambridge, MA, USA) has shown to be effective in multiple sclerosis (MS) therapy; however, the interruption of the drug has been related to a disease restart. This risk has to be carefully considered in case of accidental or desired pregnancies. Aim of the study To report the risk of disease restart in patients who interrupted NTZ because of pregnancy and discuss the implication of NTZ choice in female childbearing patients with MS. Methods Clinical histories and MRI images of four pregnant women with MS who interrupted NTZ. Results Despite pregnancy is usually related with disease stability, the cases presented here showed an abrupt increase of disability with high number of MRI lesions, some of them with a mass effect. Conclusions We recommend that female patients on childbearing age must be informed before starting NTZ treatment of the risk of a return of disease activity when the drug is discontinued. The risk occurs even during pregnancy a condition that is considered as protective for women with MS.